Illusions, objectivity, and non-reductive emergentism: Reply to Rose. (December 2022) - Cheng, Tony
In the target article, David Rose makes an interesting and substantive case against a certain kind of sceptical view: "veridical perception is impossible in principle, " combined with a certain version of anti-realism. He proceeds by first illustrating several ideas from George Orwell's seminal work, and then proposes that a certain kind of non-reductive, levelled emergentist metaphysics can help us respond to such scepticism. In this commentary, I join forces with Rose's case, but will point out that we need to take seriously two discussions in contemporary philosophy in order to make the realist case stronger: the argument from illusion and hallucination, and the causal exclusion argument. Only then do Rose and his allies can have a more satisfactory case for objectivity and realism.